Analysis of the Stimulus-Organism-Response (S-O-R) Approach to Public Interest in Paying Zakat at BAZNAS Bone Regency - Kamiruddin Naila; Mirnawati; Arifin Sahaka; Aksi Hamzah (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to empirically examine the role of zakat campaigns, zakat education, and payment convenience as determinants of public attitudes, as well as their implications for the intention to pay zakat within the Stimulus–Organism–Response (SOR) framework. Design/methodology/approach – This quantitative study was conducted at BAZNAS Kabupaten Bone involving 160 respondents selected through purposive sampling. Data were collected using Likert-scale questionnaires and analysed using SEM-PLS (SmartPLS). The outer model evaluation included convergent validity, composite reliability, Average Variance Extracted (AVE), goodness of fit, and R-squared (R²). The structural model demonstrated strong explanatory power, with R² values of 0.800 for attitude and 0.829 for intention to pay zakat. Finding/Results – The analysis results indicate that the three stimulus variables, zakat campaigns, zakat education, and payment convenience, have a positive and significant effect in shaping public attitudes towards BAZNAS as the representation of the organism component. Furthermore, public attitudes are found to exert a positive and significant influence on the intention to pay zakat as a behavioural response while also serving as a mediating variable that strengthens the relationship between stimulus and response. In addition, zakat education and payment convenience demonstrate significant direct effects on the intention to pay zakat, indicating the presence of a dual influence mechanism, both directly and indirectly through public attitudes. Originality/Value – These findings underscore the importance of enhancing the quality of zakat campaigns, zakat education, and payment systems at BAZNAS Bone Regency to strengthen positive public attitudes and increase the intention to pay zakat on a regular basis. The study implies that comprehensive and innovative zakat management strategies are essential to promote sustainable growth in zakat collection.